Time spectrum of a coherent pulse propagating through a single resonant medium. (25th August 2015) - Friedman, Y.; Steiner, J. M.; Yudkin, E.
Abstract: A new formula for the delayed electromagnetic field and the time spectrum of a coherent synchrotron radiation pulse propagating through a single resonant medium is obtained. Unlike the commonly accepted one-term formula for such a time spectrum, our formula contains an additional term arising from the secondary radiation. This term helps to overcome some shortcomings of the accepted formula. Using the experimental data from the time spectrum of an enriched stainless-steel foil obtained recently at PETRA III (DESY, Hamburg) as a test case, our new formula provides a quality fit. Unlike the commonly available computer programs used by experimentalists, our fit does not require the averaging of the thickness parameter.